Medicine and modernity : (German Historical Institute, 1997)
This collection addresses, in a comprehensive and critical fashion, fundamental issues in the history of medicine in modern Germany and considers the nature of modern German government and society in relation to Western social, political, and economic development. The central focus is on the professionalization of modern medicine and the medicalization of modern society. The problem of Nazi Germany is a recurring theme. Other topics include: hospitals in early nineteenth century society, Social Darwinism, state-run health insurance, eugenics, social control, Nazi experimentation, and the postwar medical leadership